Principles of Islamic Communication in Early Childhood Education - Amin, Afriadi; Kamila, Mahira (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
When people communicate, they seek to achieve shared meaning and share information, ideas, or attitudes with other individuals. If there is no resemblance, there will be a misunderstanding of meaning between the communicator and the communicant; alternatively, the communicant will not catch the message it receives; finally communication will not take place or not communicative. In addition, early childhood, which ranges from one to five years of age, is a very challenging time for children to understand the meaning of language; hence, communication must be considered to ensure that children are not confused. Because the data source for this research is not people but documents, this research uses a qualitative approach. In addition to using documentation techniques, researchers also use comparison methods to find common ground in the process of forming communication principles in early childhood. This research is one example of the type of research conducted in the library (library research). The type of analysis that looks at the substance of the data is called content analysis. The research findings suggest that children enter what is known as a